Cytotoxicity and inhibition of nitric oxide in lipopolysaccharide induced mammalian cell lines by aqueous extracts of brown seaweed - Jaswir I.; Monsur H.A.; Simsek S.; Amid A.; Alam Z.; bin Salleh M.N.; Tawakalit A.-H.; Octavianti F. (Japan Oil Chemists Society, 2024)
Aqueous extracts obtained from five Malaysian brown seaweeds, Sargassum duplicatum, Sargassum binderi, Sargassum fulvellum, Padina australis, and Turbinaria turbinata, were investigated for their abilities to inhibit nitric oxide (NO) production in lipopolysaccharide (LPS)-induced macrophage RAW 264.7 cell lines as well as to determine their chemical composition. The percentage yield of extracts varied among species, with P. australis having the lowest yield and T. turbinata having the highest yield. The chemical compositions of the extracts showed that the percentage of sulfate ions as well as uronic acid and total sugar content varied significantly. All extracts contained high fucose and inhibited NO secretion in a dose-dependent manner. Extracts of P. australis and T. turbinata dosed at 200 ?g/mL were able to inhibit NO secretion by > 75%. Furthermore, cytotoxicity assays revealed that some extracts were moderately toxic, while others were not. Based on these results, brown seaweed of Malaysian origin should be investigated for the production of additional anti-inflammatory compounds. 2014 by Japan Oil Chemists' Society.